OVERALL BUSINESS PLAN AND NEW PRODUCT LAUNCHING PLAN - Hoang, Thi Van Anh (Khoa Quốc tế, ĐHQGHN, 2019)
The output of this essay play an important role in business activities of Hoa Quan company. It provides Hoa Quan an over view about automotive film market with market insight (market size, market share, product and competitors, …) and customer insight. This essay also proposes to Hoa Quan a communication plan to approach target customers and activities to support sales team reach sales target.